A genetic linkage map of Vigna vexillata - Ogundiwin, E.; Thottappilly, G.; Akenova, M.E.; Pillay, M.; Fatokun, C.A. (Wiley, 2005)
Vigna vexillata is a wild cross-incompatible relative of cowpea. It is highly resistant to several diseases and pests plaguing cowpea. A linkage map was developed for V. vexillata comprising 120 markers, including 70 random amplified polymorphic DNAs, 47 amplified fragment length polymorphisms, one simple sequence repeat and two morphological traits namely, the cowpea mottle carmovirus resistance locus (CPMo V) and leaf shape (La), utilizing an F2 generation of the intra-specific cross Tvnu 1443’× Tvnu 73′. The genetic map comprised 14 linkage groups spanning 1564.1 cM of the genome. Thirty-nine quantitative trait loci (QTLs) associated with nine traits were detected on the linkage map, explaining between 15.62 and 66.58% of their phenotypic variation. Seven chromosomal intervals contained QTLs with effects on multiple traits.